Pengaruh Human Capital, Pemanfaatan Teknologi Informasi Terhadap Efektivitas Sistem Informasi Akuntansi - Constantia U, Putu Sri Devina; Sutapa, I Nyoman; Narindra, Anak Agung Ngurah Mayun (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to test and analyze the influence of human capital and information technology utilization on the effectiveness of Accounting Information Systems (AIS) at Village Credit Institutions (LPD) North Denpasar District. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to all LPD employees in North Denpasar District, totaling 118 respondents, using a census sampling technique. Data analysis was conducted using the Partial Least Squares (PLS) method with SmartPLS software. The results indicate that human capital has a positive and significant effect on the effectiveness of Accounting Information Systems, with a path coefficient of 0.590 and a p-value of 0.000. In addition, information technology utilization also has a positive and significant effect on AIS effectiveness, with a path coefficient of 0.535 and a p-value of 0.000. The coefficient of determination (R-square) value of 0.699 indicates that human capital and information technology utilization explain 69.9% of the variation in Accounting Information System effectiveness, while the remaining percentage is influenced by other factors outside the research model. These findings suggest that improving the quality of human resources and optimizing information technology utilization are essential to enhance the effectiveness of Accounting Information Systems in Village Credit Institutions.